TINJAUAN NORMATIF TERHADAP PENYELESAIAN WANPRESTASI SEWA MENYEWA KAMAR HOMESTAY ANTARA PEMILIK DAN PENYEWA HOMESTAY DI TANJUNG LESUNG KABUPATEN PANDEGLANG - Darmana, Maman Dana (LPPM Universitas Bina Bangsa, 2025)
The purpose of writing this thesis is to find out and analyze the normative review of the settlement of default on the lease of homestay rooms between homestay owners and homestay tenants in tanjung lesung pandeglang district? As for the formulation of the problem in writing this thesis is How is the implementation of default in leasing rooms between homestay owners and homestay tenants in tanjung lesung pandeglang district? What obstacles are faced in default of homestay lease in pandeglang district? Efforts to resolve defaults in homestay leases between homestay owners and homestay tenants in tanjung lesung pandeglang district? The research method used is the research used by the author is a type of research that is normative or literature. Normative is research that places the law as a building system of norms, the system of norms built is about the principles, norms, rules of legislation, court decisions, agreements, and doctrines (teachings). The results of the study concluded that the implementation of the homestay lease to the owner of the homestay tenant in Pandeglang Regency is carried out by entering into an agreement with the tenant, the renting party. Obstacles in default of lease of homestay rooms between the owner and the tenant in Tanjung Lesung, Pandeglang Regency, namely in the implementation of tenants who have made payments but have not seen the room. directly because the booking is done online. Efforts made in resolving defaults in renting homestay rooms to homestay owners and tenants of homestay rooms in Tanjung Lesung, Pandeglang Regency, namely by means of deliberation in a family manner until they find a result that has Both parties agree that the legal consequences of tenants are negligence of tenants requiring compensation, and the peace efforts of homeowners are to issue warnings and warnings to tenants in the form of kinship, and immediately resume the obligation to pay boarding rent according to the agreement in the agreement.